ANALISIS TITIK PULANG POKOK USAHATANI BAWANG MERAH (Allium ascolinicum L) VARIETAS LEMBAH PALU DI KELURAHAN TAIPA KECAMATAN PALU UTARA KOTA PALU - Abd. Rahim, Adrian (AGROTEKBIS, 2015)
This study aims to determine the total cost, production volume, selling price and the amount of revenue that the respondent farmers in the village of Taipa, so farms are run reach break-even point or in other words the farm does not lose nor gain profits. Determining the location of research done intentionally purposive, with the consideration that the Taipa Village is one of the producers of onion varieties Palu valley with a pretty good productivity in the district north of Palu. The analytical method used is the break-even point. The results showed that, total cost of cultivation of onion varieties Palu valley Rp. 20.947.755,92 per growing season, acceptance of Rp. 38,522, 362,87 per season with earned income of Rp. 17.574.606,95 per growing season, break-even point production of 93,73 kg and the break-even point at Rp. 1,874,600.